1979
DOI: 10.3109/00016357909004680
|View full text |Cite
|
Sign up to set email alerts
|

Studies on periodontal conditions in asthmatic children

Abstract: The effect of extrinsic asthma on periodontal conditions was studied in a group of 30 asthmatic children. Clinical examination revealed that asthmatic children had more gingivitis than their healthy controls. The asthmatic children who received an inhaled corticosteroid as treatment had more severe gingivitis compared with asthmatic children on disodium cromoglycate treatment. The amount of plaque was not altered. The peroxidase activity was assessed from whole saliva. The results revealed that this defense me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
1
28
0
3
Order By: Relevance
“…Studies have reported an elevated prevalence of periodontal diseases in individuals with asthma based on a dental survey among students in elementary or high schools 5 , 19 . Hyyppä et al 5 reported a similar result concerning increased risk of gingivitis in individuals with asthma and more severe gingivitis in ICS users. McDerra et al 19 also reported that children with asthma had poorer periodontal health, higher decay prevalence in their permanent teeth, and higher tooth surface loss than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported an elevated prevalence of periodontal diseases in individuals with asthma based on a dental survey among students in elementary or high schools 5 , 19 . Hyyppä et al 5 reported a similar result concerning increased risk of gingivitis in individuals with asthma and more severe gingivitis in ICS users. McDerra et al 19 also reported that children with asthma had poorer periodontal health, higher decay prevalence in their permanent teeth, and higher tooth surface loss than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the relationship between asthma and various subsequent oral disorders, including periodontal disease 5–9 . Hyyppä et al 5 have reported that gingivitis is more prevalent in children with asthma than in healthy controls, and periodontal inflammation is more severe in children using ICS treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürde astımın periodontal durumu olumsuz yönde etkileyebileceğini bildiren başka çalışmalar da mevcuttur. 5,9,13,39 Bu araştırmaların aksine, astım ile periodontal hastalık arasına ilişki göstermeyen çalışmalar da bulunmaktadır. 8,10,26 Shulman ve ark.…”
Section: Astım Ve Diş çüRüğüunclassified
“…18,19,20,21,22,23 La Federación Dental Americana ha cambiado recientemente la clasificación de riesgo de los glucocorticoides inhalados, con base en la información disponible sobre sus efectos en el crecimiento. 24 …”
unclassified